High-Frequency Recovery of Quinupristin-Dalfopristin-Resistant Enterococcus faecium Isolates from the Poultry Production Environment - Hayes, Joshua R. (American Society for Microbiology, 2001)
The occurrence of resistance to the streptogramin quinupristin-dalfopristin in Enterococcus faecium isolates from chickens on the Eastern Seaboard, was evaluated. Quinupristin-dalfopristin resistance was found in 51 to 78% of E. faecium isolates from the food production environment. The high level of resistance in this organism suggests that this reservoir of resistance may compromise the therapeutic potential of quinupristin-dalfopristin.